Does Work from Home Increase Employee Job Satisfaction? Evidence from Information Communication Technology Industry in Sri Lanka - M.M.F Rusdha; W.A Edirisooriya (International Journal of Engineering and Management Research, 2021)
The corporate world was undergoing a phase of digital transformation overrecent past years which led to adopt the work from home practice in different industry contexts and this practice had been accelerated due to the COVID-19 outbreak. To obtain the optimum outcome from employees, it is the major responsibility of the organizations to ensure that they are satisfied enough with the new work settings since employee job satisfaction is one of the significant elements of an effective workforce. Therefore,the main objective of this study was to examine the impact of work from home on employee job satisfaction in Information Communication Industry (ICT) industry in Sri Lanka. Using the survey strategy, responses were collected through questionnaires from 384 employees from the ICT industry in Sri Lanka. The findings of this study concluded that there is a positive impact of work from home on employee job satisfaction in the ICT industry in Sri Lanka as work from home gives more freedom, autonomy, and work-life balance. Further, it identified that the ICT organizations in Sri Lanka use a high level of work home practice and their employees’ job satisfaction level is also relatively high. The theoretical contribution of this study is that it extends the employee job satisfaction literature by empirically testing and validating the work from home in a new context. Also, the findings of this research are useful for all the practitioners to increase employee job satisfaction by developing flexible and unique work from home practices. Accordingly, work from home could be used as a strong motivational strategy in the ICT industry as well as in other contexts.